Qualidade de vida de pacientes com vitiligo e aspectos relacionados à extensão da lesão e índice relativo de melanina - Oliveira, Cristiane Cavalcante de (2019)
Vitiligo is a skin disease that affects between 0.4 and 2.9% of the world population and is characterized as an acquired pigmentation disorder. In it, there are acromic macules of different shapes and sizes, resulting from functional changes in melanocytes. This study aimed to evaluate the skin characteristics of vitiligo patients and quality of life in the city of Aracaju. It is an observational cross-sectional study with 28 patients from several dermatological clinics, diagnosed clinically as having vitiligo. Two research instruments were applied: a questionnaire for research on socio-demographic data, clinical and historical characteristics of the patient, and a quality of life questionnaire (Vitiligo-specific quality-oflife instrument - VitiQol). Skin characteristics were evaluated using the Courage-Khazaka Electronic, Koöln instrument and the Vitiligo Extent Score (VES) software. The mean age of the patients was 49.2 ± 12.6 years, the majority (68%) were female and married (65.5%), and the first lesion appeared from 20 to 40 years in 50% of the patients, while 85.7% of whom were experiencing stress when the first lesion appeared and the predominant reason was family issues. The predominant level of education was bachelor's degree (48.3%). 93% presented the non-segmental form and 75.9% reported a change in the lesions with stress. The mean VitiQol score was 25.3 ± 15.58 and the mean personal assessment of the severity of vitiligo was 2.39 ± 1.93. A regular correlation was observed between the quality of life determined by VitiQoL and the personal perception of the severity of the disease (item 16) (rS = 0.4317, p <0.0217). The collected data sugest that there was no correlation between QoL and the percentage of total area determined by VES and that there was a weak correlation between the relative melanin index and total QoL determined by VitiQol. That is probably due to the socio-demographic profile of the studied population, characteristic which may decrease the burden of vitiligo in the QoL or may favor patients to have a rational thought about vitiligo. Such profile, in addition, enables more access to dermatologists, treating the lesion from the beginning and decreasing its progression to other body areas.